Comparison of Motoric Block Duration between 0.5% Hyperbaric Bupivacaine and 0.5% Levobupivacaine Cesarean Section - Tanpomas, Irvan; Valentia, Clara; Suparto, Suparto; Wijaya, Monique Asby (Jurnal Kedokteran Meditek, 2025)
Introduction:The choice of anesthesia regimen affected each patient's recovery. Hyperbaric bupivacaine, a racemic mixture of S- and R-enantiomers, was more commonly used, while isobaric levobupivacaine, the S-enantiomer of bupivacaine, had fewer side effects. The anesthetic regimen chosen will determine postoperative recovery outcomes. Several studies have shown that the use of isobaric levobupivacaine accelerated postoperative motor recovery. Objectives: This study aims to compare the duration of motoric block from hyperbaric bupivacaine and isobaric levobupivacaine in pregnant women undergoing cesarean section with spinal anesthesia procedures. Methods: This quantitative analytical study was conducted on 52 cesarean section patients with spinal anesthesia procedures at Ukrida Hospital in 2024. The sample was randomly and equally divided into two groups, namely the Isobaric Levobupivacaine (IL) group of 26 people and the Hyperbaric Bupivacaine (HB) group of 26 people. Then the duration of motoric block will be assessed using the Bromage scale and observed every 30 minutes postoperatively until the patient reaches a Bromage score of 0 (can elevate the lower extremity). Results: The duration of motoric block was longer in the HB group than in the IL group (231.35 ± 16.944 versus 204.50 ± 38.472 minutes), with a significant difference (p < 0.001). Conclusion: Using the same technique and dosage, isobaric levobupivacaine with fentanyl offers faster relief of motoric block than hyperbaric bupivacaine with fentanyl.